On the issue of the formation of the Concept for the reform of civil law regulation of property rights and other property rights in the Republic of Uzbekistan - Karakhodjaeva Dilorom Mamirovna (Genius Journals, 2023)
Characterized the essence and significance of property rights in the modern market order, as well as issues of rethinking at the legislative level of the institution of property rights taking into account modern innovative trends and the needs of the economy
Keywords: property law; property rights; investment